Europakonventionen och skadeståndsrätten - Strålningseffektens konsekvenser – exempel från Sverige - Blad,Zackarias (2022)
In recent decades, tort law has undergone an extensive Europeanisation, where Sweden's approach has gone from a simple Convention-compliant interpretation of the ECHR to a discussion of the so-called radiation effect. The essay allows the radiation effect to be affirmed in two hypothetical situations in the areas of defamation and industrial action in order to examine the way in which tort disputes between individuals are affected. However, the radiation effect does not resolve the discrepancies between tort law and human rights in the area of labor law and defamation law, but instead provides a somewhat forced solution to the problems, which can certainly be argued on the basis of philosophical or constitutional arguments. In the hypothetical labor law dispute, the application of the radiation effect leads to a situation where, on the one hand, the industrial action may be considered lawful while, on the other, it gives rise to liability under the contra bonus mores principle, which cannot be seen as a practically acceptable result. In the defamation dispute, apart from the criminal law assessment, there is no basis for liability for the ECHR to be radiated upon at all. Allowing the radiation effect to have such a significant impact on a criminal assessment must be considered to be ruled out from a legality perspective, which is particularly relevant in the area of criminal law. This leaves the problem that there may be obvious violations of Convention rights at the horizontal level without any legal remedy other than a complaint to the European Court of Human Rights under Article 13.
Keywords: Skadeståndsrätt; folkrätt; civilrätt; Europakonventionen; stridsåtgärder; förtal; strålningseffekten